Application of Electrical Capacitance Method for Prediction of Plant Root Mass and Activity in Field-Grown Crops - Cseresnyés, Imre; Szitár, Katalin; Rajkai, Kálmán; Füzy, Anna; Mikó, Péter; Kovács, Ramóna; Takács, Tünde (Frontiers in Plant Science, 2018)
The root electrical capacitance (CR) method is suitable for assessing root growth and activity, but soil water content (SWC) strongly influences the measurement results. This study aimed to adapt the method for field monitoring by evaluating the effect of SWC on root capacitance to ensure the comparability of CR detected at different SWC. First a pot experiment was conducted with maize and soybean to establish CR–SWC functions for the field soil. Ontogenetic changes in root activity were monitored under field conditions by simultaneously measuring CR and SWC around the roots. The CR values were normalized using SWC data and experimental CR–SWC functions to obtain CR*, the comparable indicator of root activity. The effect of arbuscular mycorrhizal fungi (AMF) inoculation on the CR* and biomass of field-grown soybean was investigated. The pot trial showed an exponential increase in CR with SWC. CR–SWC functions proved to be species-specific. CR showed strong correlation with root dry mass (R2 = 0.83–0.87). The root activity (CR*) of field-grown crops increased until flowering, then decreased during maturity. This was consistent with data obtained with other methods. AMF inoculation of soybean resulted in significantly higher CR* during the late vegetative and early flowering stages, when destructive sampling concurrently showed higher shoot biomass. The results demonstrated that the root capacitance method could be useful for time course studies on root activity under field conditions, and for comparing single-time capacitance data collected in areas with heterogeneous soil water status.